Analisis Faktor-Faktor Penyebab Stres Kerja Terhadap Kinerja Guru: Studi Literatur Komprehensif - Satria, Rachmat; Fauzan, Fauzan; Muhammad, Al Fadil (Education and Talent Development Center Indonesia (ETDC Indonesia), 2025)
This study seeks to examine the elements contributing to work-related stress affecting teacher performance by an extensive literature review. Teacher work-related stress has emerged as a critical issue that substantially affects educational quality and teacher well-being, particularly following the profound alterations in the education system resulting from the COVID-19 epidemic. The study employs a qualitative methodology, utilizing a literature review of 20 international scientific publications published from 2014 to 2025. Thematic coding, comparative analysis, and narrative synthesis were employed in data analysis to discern consistent patterns of stress-inducing elements across various geographic contexts. The findings identified four primary categories of stress-inducing factors: work demands (administrative burden 85%, unrealistic curriculum targets 65%), relationship dynamics (conflict with parents 58%, insufficient administrative support 47%), individual factors (poor emotional regulation 52%, maladaptive perfectionism 38%), and external context (changes in educational policy 70%, technological adaptation 72%). The influence of stress on teacher performance is evidenced by a 30% decline in lesson preparation quality, a 40% discrepancy in evaluations, and a heightened intention to exit the profession. The study indicates that teachers' work-related stress is multifaceted, involving intricate interactions among organizational, interpersonal, and individual elements, and demonstrates a reciprocal relationship between teacher well-being and the sustainability of the education system, particularly during a worldwide crisis.